Doses and times of nitrogen application via leaf in the production of corn for silage in the Southern Amazon - Rosa, Fellipe Lemes da; Yamashita, Oscar Mitsuo; Carvalho, Marco Camillo de; Dallacort, Rivanildo; Rocha, Adriano Maltezo da [UNESP]; Mera, Lucas de Paula (Univ Zulia, Facultad Agronomia, 2021)
The objective was to evaluate the application of foliar nitrogen in different doses and times, as a complement to soil fertilization. The work was conducted in a rural area of the municipality of Terra Nova do Norte - MT, located in the southern of brazilian Amazon. The treatments were a combination of foliar applications of nitrogen at doses of 0, 250, 500 and 750 mL.ha(-1), and two application times with different intervals: 15 and 40 days after emergence: and 25 and 40 days after the emergency. The experimental design was a randomized block with four replications, in a factorial 4 x 2, totaling eight treatments. It was found that the variables green mass productivity and dried plant and ear and ear length responded positively as the N rates and application times. It was also observed that the foliar application of nitrogen increased the productivity of corn for silage, and better results are obtained from 750 mL.ha(-1) of the studied leaf fertilizer. There was no increase in production factors when the foliar application of nitrogen was split.
Keywords: Zea mays L.; nitrogen fertilization; foliar application; productivity